Pendampingan Pengelolaan Arsip Pada Pegawai Administrasi Kantor Hukum Rolando Marpaung & Partner - Hilda Syaf'aini Harefa; Maretta Ginting; Siska Dwi Ningsih (Fakultas Ushuluddin, Adab, dan Dakwah, 2022)
Archives are written records both in the form of pictures and charts which contain information about a subject (subject matter) or events that people make to help people's memory (that) too. The function of an archive is as a memory for a company or individual, as evidence, for human safety, and so on. Records management in an organization is very important, considering that archives are one of the evidences in an activity that has occurred. Therefore, archive management activities must always be maintained. Various information relating to organizational development and operational activities is always maintained by maintaining organizational records. Given the importance of archives, it is necessary to make efforts to improve and perfect the archive system optimally so that it can run well, efficiently and effectively. This activity aims to improve the skills of participants who are administrative employees of the Rolando Marpaung & Partner Law Office in storing and protecting records properly. The scope of this activity was carried out at the Law Office of Rolando Marpaung & Partners with all 6 (six) administrative employees participating. The results of this assistance show that based on the results of the questionnaire given to the participants, the success rate was stated to be 100%. The conclusions of this activity are (1) The implementation of this community service went smoothly according to the expectations of the community service implementation team, (2) The participants felt that this community service activity was useful, because the participants were aware of the importance of managing records for the survival of an organization, (3) The participants' responses to the community service activities carried out stated that the delivery of the material was good and the participants understood the explanations given. This is shown by the interactive atmosphere between the participants and the service team and (4) With the assistance of archive management, it facilitates the process of storing, organizing and retrieving archives.